Analysis Of Students' Ability In Solving Structured Description Problems Free Body Diagrams - Jusriana, Andi; pase, syamsinar (Al-Khazini, 2023)
The purpose of this study was to determine the ability of students in solving structured descriptions of free body diagrams for students of class XI MIA, knowing the difficulties of students in solving structured descriptions of free body diagrams for students of class XI MIA of SMA Negeri 11 Sidrap. This type of research is a mix method with 31 research subjects with structured descriptions of free body diagrams, then the test result data is analyzed for the ability to solve free body diagrams. half the sample were interviewed. Then proceed qualitatively to find the difficulty factor from the structured description of the free body diagrams. The results of the research on the ability of students to solve structured descriptions of free body diagrams in class XI MIA students of SMA Negeri 11 Sidrap on average have abilities in the good category, namely 18 people. The difficulty factor for students in solving structured free body diagrams for students in class XI MIA SMA Negeri 11 Sidrap is because students lack understanding of material, formulas, determining the direction of style arrows, branching questions, difficult to analyze questions, and do not know the work rules of the questions. . The implication of this research is that it can contribute ideas in determining policies to improve the ability of students to solve structured descriptions of free body diagrams. This means that it is expected to be a contribution and a means of scientific consideration for making policies or decisions by school principals, educators to improve the ability of students to analyze description questions.